2021
DOI: 10.3390/cancers13102378
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multi-Institutional Prediction Model for Three-Year Survival Status in Patients with Uterine Leiomyosarcoma (AGOG11-022/QCGC1302 Study)

Abstract: Background: The existing staging systems of uterine leiomyosarcoma (uLMS) cannot classify the patients into four non-overlapping prognostic groups. This study aimed to develop a prediction model to predict the three-year survival status of uLMS. Methods: In total, 201 patients with uLMS who had been treated between June 1993 and January 2014, were analyzed. Potential prognostic indicators were identified by univariate models followed by multivariate analyses. Prediction models were constructed by binomial regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“… 16 Another study showed that 8 cm or 10 cm tumor size was a significant prognostic indicator, but not 5 cm. 15 In addition, the median tumor size of uterine sarcoma reported in the previous literature was mostly 7–9 cm, 17 , 18 , 19 which was consistent with our finding (7.8 cm). Therefore, factoring in the appropriate cut‐off value and median tumor size, this study stratified the patients according to the tumor size of 7.8 cm.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“… 16 Another study showed that 8 cm or 10 cm tumor size was a significant prognostic indicator, but not 5 cm. 15 In addition, the median tumor size of uterine sarcoma reported in the previous literature was mostly 7–9 cm, 17 , 18 , 19 which was consistent with our finding (7.8 cm). Therefore, factoring in the appropriate cut‐off value and median tumor size, this study stratified the patients according to the tumor size of 7.8 cm.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Garg et al demonstrated that the 5 cm was a better cut‐off 16 . Another study showed that 8 cm or 10 cm tumor size was a significant prognostic indicator, but not 5 cm 15 . In addition, the median tumor size of uterine sarcoma reported in the previous literature was mostly 7–9 cm, 17–19 which was consistent with our finding (7.8 cm).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The FIGO staging system has been frequently applied to this disease 17,21 . However, the FIGO staging system cannot effectively and reliably stratify patients into four different prognostic groups, 13,14,25 which was also shown in this study (Figure 5A,C). This may be because STS is a very different disease entity that behaves differently from epithelial carcinoma.…”
Section: Discussionmentioning
confidence: 49%